Practice-Based Chemistry Learning with Training on Household Products Manufacturing at SMAN 15 Semarang: Belajar Kimia Berbasis Praktikum dengan Pelatihan Pembuatan Produk Household Di SMAN 15 Semarang - Sari Purnavita; Sri Sutanti; Herman Yoseph Sriyana (Mattawang: Jurnal Pengabdian Masyarakat, 2020)
The world of national education is required to be able to produce superior human resources, so that they are able to face all challenges that arise in the future. Referring to this, chemistry learning methods at the high school level need special attention. This is due to the lack of student interest in learning chemistry, because the learning is often carried out through a one-way process using the theoretical explanation method. This Community Service Program activity was carried out through workshop and training methods with practice-based chemistry learning. The training materials included liquid detergent, dish soap, and floor cleaner. The partner involved in this program was SMAN 15 Semarang. The implementation of this community service activity began with a material giving session, workshop session and training on household products manufacturing, and discussions. The results of the implementation of this community service activity can provide various benefits for the involved partner in the form of increased knowledge and understanding in the field of chemistry and motivation for entrepreneurship. Practice-based community service activities received a positive response from the partner involved in this program, so that this practice-based learning model would be applied in Chemistry learning at SMA N 15 Semarang. Abstrak Dunia pendidikan nasional harus mampu melahirkan Sumber Daya Manusia yang unggul, agar mampu menghadapi tantangan di masa depan. Salah satu metode pembelajaran yang perlu menjadi perhatian adalah pembelajaran kimia di tingkat Sekolah Menengah Atas. Pembelajaran kimia kurang diminati siswa karena pada umumnya hanya dilakukan secara satu arah dengan metode penjelasan teoritis. Kegiatan Program Pengabdian Masyarakat ini dilakukan melalui metode workshop dan pelatihan dengan pembelajaran kimia berbasis praktikum. Materi pelatihan yang diberikan meliputi detergen cair, sabun cuci piring, dan pembersih lantai. Sebagai mitra kegiatan adalah SMAN 15 Semarang Kegiatan pengabdian masyarakat dilakukan mulai dari sesi pemberian materi, sesi workshop dan pelatihan pembuatan produk household, dan diskusi. Dari hasil kegiatan pengabdian pada masyarakat , mitra mendapatkan manfaat berupa bertambahnya ilmu dan pemahaman dalam bidang kimia serta termotivasi untuk melakukan wirausaha. Kegiatan pengabdian masyarakat yang berbasis praktikum mendapat respon positif dari mitra sehingga model pembelajaran berbasis praktikum akan diterapkan dalam pembelajaran Kimia di SMA N 15 Semarang.